Mapping Digital Accessibility for Students with Disabilities: A Case Study of Aligarh’s Public Schools Under the NEP 2020 Framework - Zaidan Mansoor Alig; Farhana Syeda (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2026)
This study aims to map digital accessibility for students with disabilities in public secondary schools across Aligarh, Uttar Pradesh, under the framework of the National Education Policy (NEP) 2020. Diverging from prior studies that primarily focused on hardware counts, this research fills a critical gap by evaluating the functional usability of digital infrastructure in the local Indian context. Utilizing a mixed-methods approach with a descriptive case study design, the study audited the digital ecosystems of 40 schools using an instrument based on the POUR indicators (Perceivable, Operable, Understandable, Robust) of the WCAG 2.1 standards. Mapping results indicate a severe "hardware bias" in policy implementation; while general hardware availability reaches 85%, specific accessibility indicators such as assistive technology, alternative text (alt-text), and keyboard navigation remain at critical levels below 20%. The study concludes that mass procurement without standardized accessible content and intensive teacher training with only 5% of personnel possessing digital-inclusive pedagogical skills leads to significant budget inefficiencies. It is recommended that the government mandate WCAG 2.1 compliance as a prerequisite for procurement contracts and establish the "Aligarh Digital Accessibility Index" as a self-evaluation tool to realize a truly inclusive digital ecosystem.